RELATIONSHIP BETWEEN ACADEMIC PERFORMANCE AND GRADUATE EMPLOYABILITY IN HIGHER EDUCATION INSTITUTIONS - Norreha Othman; Zaharah Zainal Abidin; Airuddin Ahmad (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
RELATIONSHIP BETWEEN ACADEMIC PERFORMANCE AND GRADUATE EMPLOYABILITY IN HIGHER EDUCATION INSTITUTIONS This study investigates the complex relationship between academic achievement and graduate employability in the context of higher education and the changing employment market. The study looks into the relationship between graduate employability and academic achievement as measured by the cumulative grade point average (CGPA), take of value (TOV), and TOV. The study tracks changes in employability outcomes across time, including employed, jobless, increasing skills, waiting for placement, and pursuing further education. This association is dynamic, the study finds. Beyond academic accomplishments, the study also considers the value of soft skills in boosting graduates’ employability, concentrating on communication, teamwork, adaptability, and problem-solving abilities. This study offers useful insights into the debates around academic quality, practical skills, and holistic employability by addressing these issues, guiding higher education.